Next generation sequencing reveals infection of yams (Dioscorea spp.) with multiple viruses in Uganda - Ogwok, E.; Akol, Jacinta; Patil, B.L. (Wiley, 2025)
Viral diseases are common in yams (Dioscorea spp.) across Africa, caused by a diverse range of pathogens that can significantly reduce yields. Although yams in Uganda frequently display virus-like symptoms, the specific causal agents have remained largely uncharacterised. This study aimed to identify viruses infecting yams in Uganda and assess their diversity. Forty yam leaf samples—pooled from 200 symptomatic and asymptomatic plants collected from 40 fields across four central Ugandan districts—were tested for viruses. Twelve of the pooled samples were analysed by high-throughput sequencing (HTS) to identify viral sequences, while the remaining 28 were screened using conventional reverse transcription polymerase chain reaction (RT-PCR) with virus-specific primers. Three viruses were detected: yam mosaic virus (YMV) and yam mild mosaic virus (YMMV) from the genus Potyvirus, and Chinese yam necrotic mosaic virus (CYNMV) from the genus Macluravirus. Mixed infections involving up to two viral pathogens were common. Sequence analyses revealed close genetic relationships between the Ugandan isolates and those reported from Ivory Coast (YMV), Brazil (YMMV) and Japan (CYNMV). This study documents the occurrence of multiple yam viruses in Uganda for the first time, including the inaugural report of CYNMV in the country. The findings provide a critical baseline for virus surveillance, inform clean seed production systems and support the development of breeding strategies for resistance.